Strategi Negara dalam Meningkatkan Moderasi Beragama: Tinjauan atas Pola Komunikasi dan Sosialisasi Otoritatif - Wirman, Wirman; Anzaikhan, M. Anzaikhan (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2024)
This research aims to analyze the state's strategy for promoting religious moderation in Indonesia, specifically through a review of authoritative communication and socialization patterns. The research question raised is how the Indonesian government utilizes authoritative communication strategies to disseminate the values of religious moderation and how effective these efforts are in influencing public perceptions. The research method used is a literature study with a qualitative approach and descriptive analysis, where the primary sources consist of scientific journals published in the last 10 years, alongside secondary references from books, articles, and online media. The research results show that the authoritative communication pattern implemented by the government is quite effective in conveying the message of religious moderation, particularly through education, mass media, and the involvement of religious leaders. As a result, this strategy has succeeded in raising public awareness of the importance of moderation, although challenges such as radicalism and intolerance remain.